Gestión tributaria y la economía social - Estrada Tigsilema, Aracelly Marilu (2024)
Efficient tax management that considers the real needs of the population is essential to promote economic development through efficient tax collection, thus supporting sources of employment and investment in the national productive sector. The objective of this article is to analyze tax management and how it acts on the social economy, the tax benefits that encourage investment, to create employment opportunities and support the regional economy. A descriptive, exploratory, bibliographic and evaluative research methodology was applied, which will allow the development of the research. With the results obtained, the respondents consider that tax management is quite deficient due to the lack of adequate systems for the payment of taxes. It is therefore necessary to achieve a balance between the collection of direct and indirect taxes and the State should not create more taxes, but rather increase the universe of taxpayers, with incentives to tax culture, in order to eradicate tax evasion. The EPS is a sector of great importance because it supports the economic apparatus of the country, however, the current simplified regimes do not encourage investment and employment generation. The Ecuadorian government should establish a tax policy that encourages investment and employment in the EPS, through the implementation of a differentiated and reduced tax rate of.